THU0099 The localisation of flice inhibitory protein (flip) in rheumatoid synovium. (1st June 2001) - Busteed, S; Bennett, MW; Stone, M; Molloy, C; O'Connell, J; Shanahan, F; Molloy, MG
Abstract : Background: FLICE inhibitory protein (FLIP, I-FLICE) is an inhibitor of caspase 8 (FLICE) and functions as an early mediator of apoptosis. Expression of FLIP is associated with resistance to apoptosis in differentiated macrophages and also in primary B-cells and B-cell lines. The role of FLIP in rheumatoid synovium has not been fully elucidated although it has been shown that FLIP is expressed at sites of bone and cartilage erosion in the rheumatoid joint. Objectives: The aim of this study is to examine the degree of expression of FLIP in rheumatoid synovium. Methods: Samples were obtained intraoperatively from patients with rheumatoid arthritis (n = 17) and osteoarthritis (n = 9). Colon sections from patients with ulcerative colitis were used as biological controls. Immunohistochemistry was carried out using a polyclonal antibody to both the long and short forms of FLIP. Sections of synovium with prominent mononuclear infiltrates were chosen for more detailed analysis of FLIP expression in inflammatory cells. Positive mononuclear cells were counted under a high-power field and the degree of positive staining was graded using the Lindblad and Hedfors scale (see Table 1 ). Results: FLIP was strongly expressed in the synovial lining of samples from patients with both rheumatoid arthritis and osteoarthritis. There was low expression of FLIP in the rheumatoid mononuclear cells relative to the inflammatory cells in the osteoarthritis samples. Inflammatory cells in ulcerative colitis showed upregulation of FLIP. Conclusion: We conclude that the infrequency of lymphocyte apoptosis in RA synovium does not appear to be due to expression of FLIP. There is high expression of FLIP in the synovial lining in both RA and OA however. This may point to differing roles for FLIP in the regulation of apoptosis in synovium and suggests that other apoptotic regulators are involved in the persistence of inflammatory cells in rheumatoid arthritis.